Comparative Analysis of Helium-Ion Microscopy and Scanning Electron Microscopy in Nanofabrication and High-Resolution Imaging - Chen, Yun; Hu, Yufei; Li, Sixu; Wang , Chenxu (Transactions on Computer Science and Intelligent Systems Research, 2024)
With the development of science and technology, scientists’ demands for fineness in fields such as semiconductors, materials, and bioimaging are increasing day by day. Traditional electron microscopes have certain limitations in observing the microstructure of substances. The helium ion microscope (HIM) has a higher imaging resolution and more refined nano-processing capabilities, playing a breakthrough role in the development of science and technology. In this paper, the literature analysis method is used to retrieve, collect, and compare different literature. Firstly, it introduces the important role of the HIM in the fields of materials and nanofabrication. Then, it introduces the development background of the HIM and specifically analyzes its imaging principle. Next, it compares it with the scanning electron microscope, analyzes the similarities and differences between the two, and points out the problem of its high cost. Moreover, it discusses the application prospects of the HIM in high-resolution imaging and high-precision nanofabrication. Finally, it is concluded that the HIM has high accuracy and precision in the field of fine-processing materials.